P05.42 The natural course of atypical meningioma after gross total resection without adjuvant treatment. (19th September 2018) - Yoo, H; Gu, B; Byun, J; Cho, Y; Hong, S; Kim, J; Kim, C; Kim, Y
Abstract: Background: The optimal management of atypical meningioma after gross total resection remains unclear and controversial. After Simpson grade 1 resection, observation without adjuvant treatment has wide currency, while Simpson grade 4 resection, adjuvant treatment or closed observation recommended at least. In this study, the authors made a comparison with natural course of atypical meningioma after gross total resection without adjuvant treatment, especially in Simpson grade 2 resection. Material and Methods: In this study, authors reviewed 179 cases with histological proven atypical meningioma(WHO grade II) managed in single hospital between June 1990 and December 2015. A total of 62 men and 117 women were included who underwent their first surgery in our institute. Patients variably underwent adjuvant radiation therapy according to individual surgeon practices. Outcomes including overall survival and recurrence rate were analyzed using Kaplan-Meier method. Results: The average age of patients was 54.5 years. The median follow up time was 56 months. Simpson grade 1 resection without immediate postoperative adjuvant therapy was achieved in 97 patients of total 106 patients. 5-year local control rate was 82.9% and overall survival was 97.4%. 59 patients was treated with Simpson grade 2 resection and 56 patients was just under observation without adjuvant treatment. 5-year local control rate was 63.7% and overall survival was 95.2%. Conclusion: This study have performed to examine the need to adjuvant treatment for atypical meningioma after gross total resection. Patients who treated with Simpson grade 2 resection represent poor local control and shorter overall survial than Simpson grade 1 resection. The authors suggest that further adjuvant therapy should be considered even in groups of Simpson grade 2 resection, at least closed observation needed.